Diffusion-Weighted Magnetic Resonance Imaging in Maxillary Sinuses Inflammatory Diseases: Report of Three Cases and Literature Review - Luciana Munhoz; Reinaldo Abdala Júnior; Rogério Abdala; Junichi Asaumi; Emiko Saito Arita (eJournal of Oral Maxillofacial Research, 2018)
Background: Magnetic resonance imaging is considered a preferable imaging examination in the diagnosis of inflammatory maxillary sinus disease and can provide precise sinonasal characterization. Diffusion-weighted magnetic resonance imaging and apparent diffusion coefficient are complementary magnetic resonance imaging tools that can be applied to the differentiation of sinus diseases. In this report, 3 cases of inflammatory maxillary sinus diseases imaging findings considering diffusion-weighted magnetic resonance imaging features were described. Additionally, a literature review considering the use of diffusion-weighted magnetic resonance imaging in inflammatory lesions is provided.